KARAKTERISTIK FISIKOKIMIA KOMBUCHA DAUN PEGAGAN (Centella asiatica (L.) Urban) DENGAN PENAMBAHAN MADU [PHYSICOCHEMICAL CHARACTERISTICS OF KOMBUCHA FROM GOTU KOLA LEAVES (Centella asiatica (L.) Urban) WITH HONEY ADDITION] - Handayani, Ratna; Tjoa, Stefany Indah Pricilia; Rosa, Dela (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2021)
Gotu kola (Centella asiatia (L.) Urban) is a type of plant that grows in Indonesia and is generally used as a brewed drink and traditional medicine. Kombucha is a fermented beverage of tea and sugar as a fermentation substrate using a kombucha starter culture called Symbiotic Culture of Bacteria and Yeast. This research to determine the effect of honey addition and fermentation time for antioxidant activity of kombucha. Gotu kola with concentrations of 1%, 2% and 3% leafs with 12 days of fermentation. Kombucha with the best antioxidant activity added with honey and variations in fermentation time. Kombucha analyzed in the form of antioxidant activity, total phenolic, color, pH, total titrated acid, total dissolved solids, SCOBY thickness, total bacteria, total yeast, and hedonic. Gotu kola kombucha was added with 10%, 15%, and 20% honey with 4 days, 8 days, 12 days, and 16 days of fermentation. Gotu kola kombucha with the addition of 20% honey and 12 days of fermentation had the lowest IC50 amount of 4061,64±355,41 ppm, total phenolic amount of 995,8176±0,67 mg GAE/L, lightness amount of 42,34±0,07, oHue amount of 89,76±0,02, pH amount of 2,77±0,00, SCOBY thickness amount of 0,70±0,07 cm, total bacteria amount of 4,73±8,54 CFU/mL, total yeast amount of 6,72±7,33 CFU/mL, and overall acceptance 6,27±0,96. Gotu kola kombucha with the addition of 20% honey and 12 days of fermentation had the highest antioxidant activity indicated by the lowest IC value..Keywords: fermentation; gotu kola (Centella asiatica (L.) Urban); honey; IC50; kombuchaABSTRAKPegagan (Centella asiatia (L.) Urban) adalah salah satu jenis tanaman yang tumbuh di Indonesia dan pada umumnya dimanfaatkan sebagai minuman yang diseduh dan obat-obatan tradisional. Kombucha merupakan minuman yang diperoleh dari hasil fermentasi teh dan gula sebagai substrat fermentasi dengan menggunakan starter kultur kombucha yang disebut Symbiotic Culture of Bacteria and Yeast. Penelitian ini bertujuan untuk mengetahui pengaruh penambahan madu dan lama fermentasi terhadap aktivitas antioksidan kombucha. Kombucha akan dilakukan analisis berupa aktivitas antioksidan, total fenolik, warna, pH, ketebalan pelikel, total bakteri, total khamir, dan penerimaan secara keseluruhan. Kombucha daun pegagan ditambahkan madu 10%, 15%, dan 20% dengan lama fermentasi selama 4 hari, 8 hari, 12 hari, dan 16 hari. Kombucha pegagan dengan penambahan madu 20% dan lama fermentasi 12 hari memiliki nilai IC50 terendah yaitu sebesar 4061,64±355,41 ppm, total fenolik 995,8176±0,67 mg GAE/L, lightness 42,34±0,07, oHue 89,76±0,02, pH 2,765±0,00, ketebalan pelikel 0,70±0,07 cm, total bakteri 4,73±8,54 CFU/mL, total khamir 6,72±7,33 CFU/mL, dan dan penerimaan keseluruhan 6,27±0,96. Kombucha pegagan dengan perlakuan penambahan madu 20% dan lama fermentasi 12 hari memiliki aktivitas antioksidan tertinggi ditunjukkan dengan nilai IC50 yang terendah.          Kata kunci: IC50; kombucha; lama fermentasi; madu; pegagan (Centella asiatica (L.) Urban)